The Investigation on Geomechanical Properties of Shale from Semanggol Formation, Bukit Merah as Analogue to Cap Rock Integrity for Hydrocarbon Sealing - Zoolkepli, Izzaty Hannis (2016)
The integrity of shale cap rock has been an important issue in oil and gas industry as it leads to cap rock failure and hydrocarbon leakage. Cap rock integrity generally might be affected by overburden, fracturing problem or even due to injected gas during secondary production in which these factors will cause the shale to be weak as it increases the pressure within the rocks and thus results in further fracturing. Other external factors include percentage of quartz and carbonate contents in the shale itself as these factors can affect the strength behaviour of the shale. Among the available geomechanic methods to assess and analyse the cap rock integrity, Uniaxial Compressive Strength (UCS) Test has been proven to be the most practical method to be used. However, due to the difficulty in finding suitable shale cap rock to be studied, the outcrop from Semanggol Formation, Bukit Merah has been chosen to be the analogue as the formation has been proven to be originated from deep sea basin before it is uplifted and remained subaerially exposed. Based on the overall outcome of the geomechanical tests, shale from Semanggol Formation, Bukit Merah can be classified as excellent cap rock because of its high UCS value.